A Review of Modern and Traditional Approaches for the Management of Pulmonary Hypertension - Verma, Anuradha; Garg, Anshika; Ahmad, Sultan; Haider, Saquib; Kumar, Babita; Chauhan, Ritu; Singh, Manish K.; Mondal, Sambhu C. (Current Traditional Medicine, 2024)
Research Problem: Hypertension, either high blood pressure or pulmonary hypertension, both affect the life of patients in many ways. Research Questions: Does Pulmonary hypertension similar to high blood pressure? Does it affect old age people or the neonatal age groups also? What were the reasons for pulmonary hypertension? Does pulmonary hypertension manageable with modern and traditional drugs? Literature Review: The purpose of the literature review is to identify the targeted therapy for pulmonary hypertension and also include the plants that may be effective for the management of pulmonary hypertension. Conclusion: The author has reviewed many targeted drugs that are presently used, and many are in research that was found effective in making the life of patients as normal as possible. They also reviewed about 15 herbal plants which were found effective in the management of the disease. As pulmonary hypertension is not treatable, it can only be managed by changing lifestyle and food habits; therefore, the authors emphasized reviewing the traditional approach for the management of pulmonary hypertension.
Keywords: pulmonary hypertension